2018
DOI: 10.1002/etc.4257
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of microplastic impacts on consumption or growth of larval Pimephales promelas

Abstract: Microplastics are an abundant pollutant in aquatic systems, but little is known regarding their effects on larval fish. We conducted foraging and growth experiments to observe how increasing densities of microplastics (polyethylene microspheres) impact the foraging and growth of Pimephales promelas larvae. We found minimal impacts on larval consumption of Artemia nauplii in the consumption study, as well as little impact on total length after 30 d of the growth experiment. Environ Toxicol Chem 2018;37:2912-291… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…The SGR was an important index to measure the economic benefits of fisheries, and the larger the value was, the greater of fish would be. Malinich et al ( 2018 ) found that MPs had no impact on the growth of the fathead minnow Pimephales promelas , and a similar result was detected from the brown trout Salmo trutta (Jakubowska et al, 2020 ). However, MPs could induce growth inhibition in the common carp Cyprinus carpio .…”
Section: Discussionmentioning
confidence: 78%
“…The SGR was an important index to measure the economic benefits of fisheries, and the larger the value was, the greater of fish would be. Malinich et al ( 2018 ) found that MPs had no impact on the growth of the fathead minnow Pimephales promelas , and a similar result was detected from the brown trout Salmo trutta (Jakubowska et al, 2020 ). However, MPs could induce growth inhibition in the common carp Cyprinus carpio .…”
Section: Discussionmentioning
confidence: 78%
“…Endpoints studied at the population level comprise fish fecundity (e.g. number of eggs laid and hatching rate) (Cong et al 2019;LeMoine et al 2018;Wang et al 2019c), embryo survival and development (Batel et al 2018;Pitt et al 2018) and larval survival, development and behaviour (Chen et al 2017;Choi et al 2018;Malinich et al 2018). Endpoints at the ecosystem levels relate to behaviour and include feeding behaviour (e.g.…”
Section: Chordata: Fishmentioning
confidence: 99%
“…Endpoints at the ecosystem levels relate to behaviour and include feeding behaviour (e.g. feeding time, foraging, predatory performance), environment exploration and fish locomotion (Cedervall et al 2012;Choi et al 2018;Critchell and Hoogenboom 2018;de Sá et al 2015;Ferreira et al 2016;Fonte et al 2016;Guven et al 2018;Jacob et al 2019;Luís et al 2015;Mak et al 2019;Malinich et al 2018;Mattsson et al 2017;Pitt et al 2018;Skjolding et al 2017;Tosetto et al 2017;Wen et al 2018a). Contrary to the above-described levels of biological organization, for which the numbers of impacted and non-impacted endpoints are similar, at the individual level more studies report an absence of effects (11 studies) than the observation of adverse effects (3 studies) following microplastic exposure.…”
Section: Chordata: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our results, studies assessing the ecotoxicity of PE MPs on fish exposed via trophic chains also reported no effects [37][38][39] . Moreover, most studies exposing fish via water showed either no effects 34,[40][41][42][43] or mild effects, which include inhibition of AChE activity, impaired energy reserves, decreased swimming and predatory performances, changes in plasma biochemistry and histological changes in gills [44][45][46][47][48] . The adverse effects observed with pristine PE MPs in these studies could be due to the presence of monomers or additives 5 sorbed on MPs but that were not reported, either because no chemical analysis was performed or because concentrations were below limits of detection.…”
Section: Effect Of Contaminantsmentioning
confidence: 99%